Analisis Stres Akademik pada Mahasiswa yang Bekerja dengan Menggunakan Metode Fuzzy Logic(Studi Kasus: Mahasiswa Prodi Sistem Informasi Unpam Kampus Serang) - Stevanes, Stevanes; Septiani, Selly (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2025)
Students who work are at risk of experiencing higher academic stress due to the dual burden of work and study. This study aims to analyze the level of academic stress among students in the Information Systems Program for working adults (Regular C Saturday) at UNPAM Serang using a fuzzy logic approach. The method used is the Mamdani Fuzzy Inference System through five main stages: fuzzification, rule base formation, inference process, defuzzification, and result interpretation. The testing was conducted through MATLAB application calculations and manual calculations, with accuracy evaluated using the Mean Absolute Percentage Error (MAPE). The test results showed that the difference in results between the manual method and MATLAB was very small, with a MAPE value of 0.843%, indicating that MATLAB has a very high accuracy rate in classifying academic stress into the categories of no stress, low stress, moderate stress, and high stress. These findings prove that fuzzy logic is effective for measuring psychological variables that are difficult to capture conventionally. Additionally, this approach has the potential to be developed as a tool for early detection of psychological conditions among students in higher education settings.